Strategies for Exploiting Technological Innovations: When and When Not to License - Hill, Charles W. L. (Organization Science, 1992)
Given the limits of the patent systems, an innovating firm faces a difficult strategic conundrum: should it license its new technology to competitors or not? If the innovating firm does not license its new technology, competitors may quickly develop their own, possibly better, version of the technology. On the other hand, if imitation of the new technology is difficult, by denying its technology to competitors the innovating firm may be able to establish a competitive advantage. If the innovating firm does license its new technology to competitors, it runs the risk of losing control over that technology (of giving away its competitive advantage to competitors). On the other hand, if competitors are able to rapidly imitate the new technology anyway, by licensing its technology the innovating firm may ensure that its version of the technology becomes the dominant design in an industry. Moreover, the innovating firm will receive royalty payments in this scenario. Given these different scenarios, what should an innovating firm do? In this paper a theoretical framework is constructed that identifies the factors that influence an innovating firm's choice between licensing and not licensing. This suggests that the speed of imitation, the extent of first mover advantages, and the transaction costs of licensing play a major role in determining the appropriate choice.